2022
DOI: 10.1111/ijfs.16224
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐hypercholesteraemic and antioxidative activities of camel skin gelatin hydrolysate: effect of enzyme type, enzyme: substrate ratio and time of hydrolysis

Abstract: Summary Camel skin gelatin hydrolysate (CSGH) was prepared using different proteolytic enzymes [alcalase (A), protease (P) and their combination (AP (1:1))], hydrolysis time (2, 4 and 6 h) and enzyme: substrate (E/S) ratio (1%, 3% and 5%). In general, the degree of hydrolysis (DH) increased with increasing hydrolysis time for all enzyme treatments. CSGHs generated with alcalase showed significantly higher lipase (LP) inhibitory activity compared with protease‐derived CSGH at all hydrolysis conditions (P < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Donkey-hide gelatin hydrolysates were found to have immune modulation properties in lipopolysaccharide-stimulated RAW264.7 macrophages [ 11 ]; while tilapia-skin gelatin hydrolysates, with chemical phosphorylation, have an increased calcium-binding capacity [ 12 ]. Moreover, camel-skin gelatin hydrolysate was revealed to have both antihypercholesteremic and antioxidative effects [ 13 ]. It was reported that collagen and gelatin hydrolysates possess the desirable function of enhancing bone mineral density [ 14 ] and increase the content of organic substances in the bone [ 15 ] but decrease osteoclast activity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Donkey-hide gelatin hydrolysates were found to have immune modulation properties in lipopolysaccharide-stimulated RAW264.7 macrophages [ 11 ]; while tilapia-skin gelatin hydrolysates, with chemical phosphorylation, have an increased calcium-binding capacity [ 12 ]. Moreover, camel-skin gelatin hydrolysate was revealed to have both antihypercholesteremic and antioxidative effects [ 13 ]. It was reported that collagen and gelatin hydrolysates possess the desirable function of enhancing bone mineral density [ 14 ] and increase the content of organic substances in the bone [ 15 ] but decrease osteoclast activity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%